Evaluation of haemoglobin cut-off for mild anaemia in Asians - analysis of multiple rounds of two national nutrition surveys - Varghese, Jithin Sam (Indian J Med Res, 2019)
BACKGROUND & OBJECTIVES: The haemoglobin (Hb) cut-off is a single value for all populations. It is possible that different populations might have slightly different cut-off values; but, this needs to be evaluated in healthy populations with low possibility of inadequate dietary intakes of haematopoietic nutrients. This study was conducted to assess the existence of race-specific Hb cut-offs for mild anaemia in healthy populations and their potential implications. METHODS: In this study the Hb distributions of healthy White, Black, Mexican and Hispanic and Asian non-pregnant women obtained from nine rounds of the National Health and Nutrition Examination Survey (NHANES) and two rounds of National Diet and Nutrition Survey (NDNS), was examined to check the existence of race-specific Hb cut-off for mild anaemia, by standard statistical methods. RESULTS: The mean Hb of Blacks, Mexicans and Hispanics and Asians were lower than Whites, consistent with previous literature. The Hb cut-off for mild anaemia in Asians was lower at 11.22 g/dl. INTERPRETATION & CONCLUSIONS: Using the Hb cut-off derived in this study in place of the World Health Organization, cut-off of 12 g/dl would result in a 17.9 per cent decrease in the prevalence of anaemia in India. This points to the need for re-examining race-specific cut-off for mild anaemia and points to the need for alternative methods, perhaps linked to risk of unhealthy outcomes.